Professor Ivan Mykolayovych Ishchenko — Heracles of Ukrainian medicine - Lytvynenko, N. P.; Holik, O. V.; Zavernyi, L. G.; Kryvopustov, M. S.; Tsiura, Y. P.; Tarasiuk, T. V. (General Surgery, 2023)
The article focuses on the professional and scientific path of Professor Ivan Mykolayovych Ishchenko. He was a leading Ukrainian surgeon, a renowned scientist, an accomplished teacher, and a great humanist who formed the ideology of surgical science. Professor Ishchenko defined and developed promising directions for scientific research in the fields of military field surgery, urology, traumatology, neuro‑ and thoracic surgery, and tissue transplantation. His scientific interests included the surgical treatment of diseases of the biliary tract, liver, and stomach as well as theoretical and practical issues of anesthesia administration.